Transplanted Human Glial-Restricted Progenitors Can Rescue the Survival of Dysmyelinated Mice Independent of the Production of Mature, Compact Myelin - Lyczek, Agatha (Exp Neurol, 2017)
The therapeutic effect of glial progenitor transplantation in diseases of dysmyelination is currently attributed to the formation of new myelin. Using magnetic resonance imaging (MRI), we show that the therapeutic outcome in dysmyelinated shiverer mice is dependent on the extent of cell migration but not presence of mature and compact myelin. Human or mouse glial restricted progenitors (GRPs) were transplanted into rag2(−/−) shiverer mouse neonates and followed for over one year. Mouse GRPs produced mature myelin as detected with multi-parametric MRI, but showed limited migration without extended animal lifespan. In sharp contrast, human GRPs migrated extensively and significantly increased animal survival, but production of mature myelin did not occur until 46 weeks post-grafting. We conclude that human GRPs can extend the survival of transplanted shiverer mice prior to production of mature myelin, while mouse GRPs fail to extend animal survival despite early presence of mature myelin. This paradox suggests that transplanted GRPs provide therapeutic benefits through biological processes other than mature myelin capable to facilitate rapid conduction, challenging the current dogma of the role of myelin in the function of the central nervous system.